Caspar David Friedrich and the subject of landscape - Koerner, Joseph Leo (Reaktion, 2009)
Caspar David Friedrich (1774-1840) is heralded as the greatest painter of the Romantic movement in Germany, and Europe's first truly modern artist. His mysterious and melancholy landscapes, often peopled with lonely wanderers, are experiments in a radical
Keywords: Friedrich, Caspar David, : 1774-1840 : Criticism and interpretation; Landscapes in art; Romanticism in art : Germany